Application research of mixed teaching mode based on Wechat applet. Issue 3 (April 2020) - He, Fen
Abstract: in the era of rapid development of mobile Internet, Wechat applet because it does not need to install and uninstall characteristics, become a very popular application. Wechat applet applied to teaching is a new teaching auxiliary means. Firstly, the feasibility of WeChat is analyzed from the perspective of function and students' willingness to use it. Then it discusses the application strategy of Wechat applet in the course of database application technology teaching. Finally, through the analysis of the effect of Wechat applet auxiliary course teaching, it is shown that Wechat applet is an effective auxiliary means of classroom teaching, which can be promoted and applied in other courses.